Peliosanthes qixingkengensis (Asparagaceae), a new species from Guangdong Province, Southern China - Feng, Hui-Zhe; Chen, Xiao-Yun; Li, Xiao-Feng; Liang, Jun-Jie; Liao, Wen-Bo; Wu, Lin-Fang; Fan, Qiang (Phytotaxa, 2025)
Peliosanthes qixingkengensis, a new species from Guangdong Province, southern China, is distinguished by a unique combination of morphological traits: (1) a flattened and split corona; (2) a 3–6-lobed stigma and a 3–6-locular ovary. Furthermore, persistent cataphylls (membranous sheaths encasing petioles, up to 14 cm long) provide additional diagnostic characters differentiating it from congeners.